(untitled)
Crayfish, lobster, and sea-water samples collected from five fishing islands on the Atlantic coastBight of Biafra (Bonny)belonging to Ibaka Local Government Area of Akwa-Ibom State of Nigeria were bacteriologically evaluated on thiosulphate citrate bile-salt sucrose (TCBS) agar for Vibrio load and pathotypes. Mean log10 Vibrio counts of 7.64